Sex differences in lower extremity kinematics during overhead and single leg squat tests - Lisman, P.; Wilder, J. N.; Berenbach, J.; Foster, J. J.; Hansberger, B. L. (Sports Biomechanics, 2024)
The Overhead Squat (OHS) and Single-Leg Squat (SLS) are two clinical tests used by practitioners to identify high-risk biomechanical movement patterns. Several published studies have reported sex differences in SLS performance; however, few have investigated variations during the OHS and none has measured kinematics with a marker-less motion capture system. Therefore, this study aimed to compare biomechanical movement patterns between male and female collegiate athletes during OHS and SLS testing. Seventy-five females and 58 male athletes completed OHS and SLS . A Microsoft Kinect sensor using Athletic Movement Assessment software (PhysiMax) was used to measure kinematics. For the OHS, males displayed greater peak knee frontal plane projection angles (FPPA) (M:26°±10°, F:20°±8°; P <0.05), peak hip flexion (M:-94°±14°, F:-87°±15°; P <0.05), and peak trunk flexion angles (M:11°±11°, F:6°±9°; P <0.05). For the SLS (dominant-limb), males displayed greater peak trunk flexion (M:32°±6°, F:27°±7°; P <0.05). For the non-dominant limb, females displayed greater peak knee FPPA (F:-12°±9°, M:-8°±9°; P <0.05) whereas males displayed greater peak trunk flexion angles (M:32°±5°, F:27°±7°; P <0.05). These findings suggest the need for practitioners to develop sex-specific corrective exercise programmes in effort to improve lower extremity kinematics in athletes.